O caso Izidora: as ocupações urbanas e a reprodução do espaço em Belo Horizonte - Guilherme de Abreu Bastos Lima Rodrigues (2016)
This work investigates the Izidora Case, a social conflict of huge proportions that involves a terrain occupied by eight thousand families, in order to show how its dynamics operates. We begin by situating its historical roots in the context of the urban development of Belo Horizonte, presenting the State´s role in this process; then, we introduce some theoretical resources aiming to build a conceptual framework to elucidate this conflict. After that, we bring the hypothesis in which the role of social movements is crucial on the reproduction of space in this region. Finally, we try to read the conflict in a way that signalizes some tendencies and possibilities for its break up.